Conductance of 'bare-bones' tripodal molecular wires. Issue 42 (28th June 2018) - Davidson, Ross J.; Milan, David C.; Al-Owaedi, Oday A.; Ismael, Ali K.; Nichols, Richard J.; Higgins, Simon J.; Lambert, Colin J.; Yufit, Dmitry S.; Beeby, Andrew
Abstract : When venturing into the field of tripodal molecular conductors the geometry of the tripod with respect to the surface is a critical factor affecting conductance. Here we examine the behaviour of a tripodal conductor by systematic modifications of a triarylphosphine system. Abstract : Controlling the orientation of molecular conductors on the electrode surfaces is a critical factor in the development of single-molecule conductors. In the current study, we used the scanning tunnelling microscopy-based break junction (STM-BJ) technique to explore 'bare-bones' tripodal molecular wires, employing different anchor groups (AGs) at the 'top' and 'bottom' of the tripod. The triarylphosphine tris(4-(methylthio)phenyl)phosphine and its corresponding phosphine sulfide showed only a single high conductance feature in the resulting 1- and 2-dimensional conductance histograms, whereas analogous molecules with fewer than three thiomethyl AGs did not show clear conductance features. Thus, by systematic molecular modifications and with the aid of supporting DFT calculations, the binding geometry, with respect to the surface, was elucidated.